Modulation of Hepatitis C Virus Genome Replication by Glycosphingolipids and Four-Phosphate Adaptor Protein 2 - Khan, Irfan (J Virol, 2014)
Hepatitis C virus (HCV) assembles its replication complex on cytosolic membrane vesicles often clustered in a membranous web (MW). During infection, HCV NS5A protein activates PI4KIIIα enzyme, causing massive production and redistribution of phosphatidylinositol 4-phosphate (PI4P) lipid to the replication complex. However, the role of PI4P in the HCV life cycle is not well understood. We postulated that PI4P recruits host effectors to modulate HCV genome replication or virus particle production. To test this hypothesis, we generated cell lines for doxycycline-inducible expression of short hairpin RNAs (shRNAs) targeting the PI4P effector, four-phosphate adaptor protein 2 (FAPP2). FAPP2 depletion attenuated HCV infectivity and impeded HCV RNA synthesis. Indeed, FAPP2 has two functional lipid-binding domains specific for PI4P and glycosphingolipids. While expression of the PI4P-binding mutant protein was expected to inhibit HCV replication, a marked drop in replication efficiency was observed unexpectedly with the glycosphingolipid-binding mutant protein. These data suggest that both domains are crucial for the role of FAPP2 in HCV genome replication. We also found that HCV significantly increases the level of some glycosphingolipids, whereas adding these lipids to FAPP2-depleted cells partially rescued replication, further arguing for the importance of glycosphingolipids in HCV RNA synthesis. Interestingly, FAPP2 is redistributed to the replication complex (RC) characterized by HCV NS5A, NS4B, or double-stranded RNA (dsRNA) foci. Additionally, FAPP2 depletion disrupts the RC and alters the colocalization of HCV replicase proteins. Altogether, our study implies that HCV coopts FAPP2 for virus genome replication via PI4P binding and glycosphingolipid transport to the HCV RC. IMPORTANCE Like most viruses with a positive-sense RNA genome, HCV replicates its RNA on remodeled host membranes composed of lipids hijacked from various internal membrane compartments. During infection, HCV induces massive production and retargeting of the PI4P lipid to its replication complex. However, the role of PI4P in HCV replication is not well understood. In this study, we have shown that FAPP2, a PI4P effector and glycosphingolipid-binding protein, is recruited to the HCV replication complex and is required for HCV genome replication and replication complex formation. More importantly, this study demonstrates, for the first time, the crucial role of glycosphingolipids in the HCV life cycle and suggests a link between PI4P and glycosphingolipids in HCV genome replication.